Strategy for Developing Human Resources Through Employee Productivity in the Working Environment during Pandemic ( Study on MSME Employees Stay Kopi-Kopian East Jakarta ) - Sri Rejeki (East Asian Journal of Multidisciplinary Research, 2022)
In this era of globalization, business actors need to be more creative and innovative in building their businesses in order to compete with new competitors. One of the most popular and trending businesses is retail, especially the coffee shop sector. The coffee shop business has become a phenomenon and is currently an attraction for the people of cities in Indonesia. The purpose of this study is to determine human resources through employee productivity in the work environment and to find out the strategies that must be carried out by Stay Kopi-Kopian SMEs regarding improving the quality of human resources for their employees to achieve better productivity results. Data collection in this study was conducted through interviews. MSME employees of Stay Kopi-Kopian must develop human resources in their work environment. Suggestions in this study are that the employees of MSME Stay Kopi-Kopian should be given training provided by the makers of the MSME Stay Kopi-Kopian or the government that provides training, so that with this training employees have quality human resources.